Limits of processing personal data in digital transactions - Lemouchi, Adel (The International tax journal, 2025)
Digital transactions are no longer confined to one field but have spread to almost all areas, and there is no escape from them. One of the requirements of these transactions is the necessity to declare personal data, which is referred to as digital privacy and is legally protected. However, this protection may not extend to data voluntarily provided by the individual involved in the transaction. Therefore, there is a need to establish regulations and limits for data collectors and processors that take into account the nature of the transaction, the purpose of processing, the principle of adequacy, and the necessity of digital forgetting.